C19EpidemiologyGraphs: A Spatial Graph Database with Global COVID-19 Epidemiological Vertex Features - Torres, Artur B.; Moreira, Gladston J. P. (Anais do Dataset Showcase Workshop (DSW); 2026: Anais do VIII Dataset Showcase WorkshopDO - 10.5753/dsw.2026.249568, 2026)
Adding spatial relationships to a collection of independently reported pieces of data can be a challenging prerequisite before using spatial-aware tools, such as graph neural networks. At the same time, epidemiological research could benefit from the spatial awareness these tools provide while exploring new epidemic models. With this in mind, we introduce C19EpidemiologyGraphs, a global and multi-aggregation level spatial graph database embedded with vertex-level features related to COVID-19 epidemiology, where vertices are reporting locations and edges indicate that two locations share a border. To the best of our knowledge, this is the first public database to integrate spatial graphs with COVID-19 epidemiological data at a large scale.